From empire to inequality: Lessons from the Mughal collapse for today’s social divides - Utari, Muhammad; Hawari, Ilham Faisal; Badruzzaman, Puad; Hernawan, Wawan; Kusdiana, Ading (FISIP UIN SGD Bandung, 2025)
This study aims to analyze in depth the process of the decline and collapse of the Mughal Dynasty (1526–1857), an important event in the history of South Asia that was influenced by a variety of complex factors, both internal and external. Using historical research methods that include heuristic stages, source criticism, interpretation, and historiography, the study relies on primary sources such as Ain-i-Akbari, Akbarnama, and Tuzuk-i-Jahangiri, as well as secondary literature from relevant modern historians. The results of the study show that the collapse of the Mughal Dynasty was not caused by a single factor, but was an accumulation of various structural problems and geopolitical dynamics. Significant internal factors include the weakening of the jagirdari system, repeated succession crises, corrupt bureaucracy, and weak leadership after Aurangzeb's reign. Meanwhile, external factors included invasions from Persia and Afghanistan, the rise of regional powers such as the Maratha and the Sikhs, and the aggressive expansion of the British East India Company, which gradually eroded Mughal sovereignty. This study concludes that the collapse of empires is the result of adaptive failures in dealing with structural challenges and changes in the regional political-economic landscape. The implications of this study broaden our understanding of the dynamics of imperial power disintegration and the transition to colonialism in India. This paper lies in a holistic and systematic approach that links the collapse of the Mughals with the theory of the fall of empires from the perspective of global historiography. Contribution: By linking the collapse of the Mughal Empire to broader theories on imperial decline and the transition to colonialism, this research broadens the understanding of imperial disintegration and enriches global historiographical perspectives on empire fall.